Effect of Ethanol Extract of Soursop (Annona muricata Linn.) Leaves on Intestinal Motility of Mice (Mus musculus) Induced by Oleum Ricini - Alvirosa, Agil Noviar; Rahardjo, Setyo Sri; Suparyanti, Endang Listyaningsih (Nexus Biomedika, 2016)
Introduction: Diarrhea is one of major problem in the world. There are about 2 billion cases of diarrhea with a mortality rate of 1.5 million per year in the world. Diarrhea is the first cause of death in infants and toddler, while in all age groups is the fourth leading cause of death in Indonesia. One of the pathogenesis of diarrhea is an increase of intestinal motility. Leaves of soursop (Annona muricata Linn.) contains tannins, flavonoids and steroids which effect of intestinal antimotility. This study aims to prove that the ethanol extract of soursop leaves may inhibit intestinal motility in mice induced by oleum ricini. Methods: This study was a laboratory experimental with posttest only controlled group design. Samples were 30 Swiss Webster male mice, aged 2-3 months, and weight Â± 20 g. The samples were divided into 5 groups, namely Negative Control Group (KKN), Positive Control Group (KKP), Treatment I Group (KP1), Treatment II Group (KP2), and Treatment III Group (KP3) were respectively given distilled water; loperamide HCl; ethanol extract of soursop leaves with dose of 5.6 mg/20 g BW; dose of 11.2 mg/20 g BW; and dose of 22.4 mg/20 g BW. After 60 minutes, all of mice were given oleum ricini and it was waited until 45 minutes. Then all of mice were given 10.0% activated carbon suspension in 3.0% pulvis gummi arabicum and left for 20 minutes. Furthermore, the mice were sacrificed by spinal dislocation and their intestines were removed. Length of intestine through by activated carbon marker was measured and compared to the length of intestine entirely. Data were analyzed by One Way ANOVA and Post Hoc Multiple Comparisons LSD (Î± = 0.05). Results: One Way ANOVA test results showed significant differences between the five groups with p = 0.000 (p < 0.05). The test results Post Hoc Multiple Comparisons LSD showed significant differences (p < 0.05) between KKN and KKP (p = 0.000), KKN and KP2 (p = 0.000), KKN and KP3 (p = 0.000); whereas there is no significant difference (p > 0.05) between KKP and KP3 (p = 0.810). Conclusion: The ethanol extract of soursop (Annona muricata Linn.) leaves can inhibit intestinal motility in mice (Mus musculus) induced by oleum ricini. Keywords: soursop leaves, oleum ricini, intestinal motilityÂ